Connectivity and Rural Development: Examining India's Rural Road Construction Scheme - Santosh Kumar; Monica Shandal; Ariel Zucker (Institute of Labor Economics (IZA), 2025)
We examine the impact of rural road connectivity on economic and social outcomes in the context of India's PMGSY, the world's largest rural road program. Using a novel village-level survey explicitly designed around PMGSY's rollout, we exploit quasi-random variation in road placement to estimate causal effects. We find that roads increase producer prices by 1.4 SD, reduce consumer prices by 0.6 SD, shift labor from agriculture to local casual work, and decrease short-term migration. Additionally, road connectivity improves governance, delays marriages, and improves wedding quality. Our findings highlight the role of infrastructure in shaping rural economies and social institutions.
Keywords: I15; J43; O12; O18; R23; R42; 330; migration; wages; prices; PMGSY; rural roads; India